076 The expanding clinical phenotype of NMDAR encephalitis. Issue 6 (24th May 2018) - Qiu, Jessica; Helou, Jacob; Urriola, Nicholas; Welgampola, Miriam; Parratt, John; Wong, Toh Hock; Parratt, Kaitlyn
Abstract : Introduction: The classic phenotype of anti-N-methyl-d-aspartate receptor (NMDA-R) encephalitis is a constellation of prodromal psychiatric symptoms, seizures, movement disorder and progressive autonomic dysfunction, frequently associated with ovarian teratoma. We describe four cases illustrating the expanding phenotype of NMDA-R encephalitis. We present two cases from two tertiary hospitals Case 1 A 31 year old woman presented with focal onset seizures. She developed epilepsia partialis continua. CSF and serum NMDA-R antibodies were detected and PET of the brain showed bi-frontal hyper-metabolism. The seizures resolved with immunotherapy. Case 2 A 26 year old woman presented with vomiting and dysequilibrium. She was found to have torsional downbeat nystagmus with otherwise normal eye movements and vestibulo-ocular reflexes. She developed bilateral appendicular and truncal ataxia, head bobbing and ocular flutter. PET demonstrated diffuse cerebellar hyper-metabolism. CSF NMDA-R antibodies were detected and an ovarian teratoma was identified. Case 3 A 67 year old right-handed woman was treated for HSV encephalitis. MRI of the brain demonstrated typical changes in the right anteromedial temporal lobe, inferior frontal lobe and insular cortex. Five months later, she deteriorated with progressive cognitive dysfunction and prominent orofacial dyskinesia. Initially both CSF and serum were negative for NMDAR antibodies, but repeat CSF and serum were positive. Case 4 A 61 year old woman presented with progressive cognitive impairment over eight months initially characterised by difficulty with calculations and making mistakes at work but subsequent severe impairment of language, executive function and memory and the development of facile and disinhibited behaviour. PET demonstrated mesial bi-temporal hyopo-metabolism and NMDA-R antibodies were detected in serum. She recovered with immunotherapy. Conclusion: NMDA-R encephalitis should be considered in various neurological presentations including explosive onset focal epilepsy, rapidly progressive dementia, post HSV encephalitis and rhombencephalitis. Early detection is important given the frequent response to immunotherapy.